Long-term evaluation of outcomes and survival of patients treated for retinoblastoma - Krzysztof Morawski; Agata Janosz-Maduzia; Tomasz Haładus; Justyna Jędrychowska-Jamborska (Elsevier, 2020)
Purpose: The purpose of our study was to assess long-term outcomes of patients suffering from retinoblastoma who underwent systemic chemotherapy using vincristine, etoposide, and carboplatin (VEC protocol) followed by other local treatments. Material and methods: A retrospective review of patients diagnosed with retinoblastoma from 1997 to 2012 in the Department of Ophthalmology and Ocular Oncology of the University Hospital in Krakow was performed. A total of 58 eyes of 42 patients were analyzed. The main outcome measures were survival rate of the patient, final visual acuity, preservation of affected eyeball, intraocular relapse, extraocular orbital tumor recurrence, and occurrence of other neoplasms. Results: The overall survival rate was 97.6%. The majority of eyes (67.2%) had retinoblastomas of group V in the Reese-Ellsworth Classification (REC). Ocular preservation was achieved in 41.4% eyes. Of the 24 preserved eyes, 41.7% had a final visual acuity of 6/12 or better, 12.5% had visual acuity worse than 6/12 but better than 6/60, and 45.8% had visual acuity of 6/60 or worse. Three patients (7.1%) experienced orbital recurrence of retinoblastoma and one patient (2.4%) developed a second malignancy (chronic myeloid leukemia associated with the Philadelphia chromosome). Conclusions: Retinoblastomas, especially in Reese-Ellsworth group V (RE group V), not only impair vision, but may lead to metastases and death. Early diagnosis and prompt treatment are essential to salvage the eye and vision, and to avoid metastases. Long-term follow-up of retinoblastoma survivors is important to identify late effects associated with treatment and the occurrence of second malignancies.